Impact of COVID-19 restrictions on thyroid cancer diagnoses in a comprehensive cancer center (2017–2023) - Hayley Mann; Erin Dimon; Yichi Zhang; Natalia Arroyo; Abdullah Adil; Yanchen Zhang; Oguzhan Alagoz; Sara Fernandes-Taylor; Erin J. Aiello Bowles; Louise Davies; David O. Francis (PLoS ONE, 2026)
Introduction The Coronavirus 2019 (COVID-19) pandemic disrupted healthcare delivery across the United States, leading to a sharp decline in outpatient visits. Given that thyroid nodule evaluation and diagnosis typically occur in outpatient settings, we hypothesized that these disruptions would reduce thyroid cancer incidence. This study evaluates trends in thyroid cancer diagnosis, treatment, and outcomes at a U.S. comprehensive cancer center from 2017 to 2023. Methods We included adults with pathologically confirmed thyroid cancer diagnosis between January 1, 2017, and December 31, 2023. Primary analyses assessed (1) annual percent change (APC) in thyroid cancer incidence from 2017–2023 and (2) incidence trends across three periods: pre-pandemic (Jan 2017–Mar 2020), pandemic (Apr 2020–Mar 2021), and COVID-years (Apr 2021–Dec 2023). Annual incidence rates were calculated using the total number of individuals cared for within our health system each year as the denominator. Secondary outcomes included tumor size, extent and timing of surgery, and 1-year all-cause mortality across time periods. Results Among 1,031 patients (68% women, 92% White, mean age 52 ± 15.5), age- and sex-adjusted thyroid cancer incidence declined from 34 to 15.6 per 100,000 persons between 2017 and 2022, with an average APC of –14.4%. Diagnoses rose slightly in 2023 (21 per 100,000) compared to 2022 but remained 38% below 2017 levels. No significant differences were observed in tumor size, surgical treatment, gender ratio, or 1-year all-cause mortality across timeframes. Conclusion Age- and sex-adjusted annual incidence of thyroid cancer declined steadily from 2017 to 2022. The annual decrease in thyroid cancer continued through the pandemic years. Tumor size and mortality remained stable across all years evaluated. The increase in diagnoses noted in 2023 may be a correction due to missed cases during the years of the pandemic or could represent a new steady state incidence after years of decline.